Sediment oxygen demand rate in a flow regulated lagoon (Venice, Italy) - Leoni, Simone; Dominik, Janusz; Cassin, Daniele; Manfè, Giorgia; Tagliapietra, Davide; Acri, Francesco; Zonta, Roberto (Frontiers in Environmental Science, 2022)
From October 2020, the MOSE system went into operation in the three inlets to protect Venice and its lagoon from flooding caused by high tide events in the Adriatic Sea. While the MOSE increases the prospect of physical defense, how will the new status of a regulated lagoon affect the functioning of the waterbody? In particular, the dissolved oxygen balance in the water column can be affected by the expected increase in water residence times. Sediments play an important role in oxygen consumption in the water column and for this reason sediment oxygen demand (SOD) was studied in situ for the first time, in 16 sites at four lagoon areas. SOD rate, measured throughout 2021 with specially made benthic chambers, varied in the different areas and with seasons (from 0.63 to 24.00 g m-2 d-1), with higher values at the more confined sites and significantly lower values in those belonging to the open lagoon. Based on SOD rate, consumption times of dissolved oxygen in the water column were estimated at the MOSE closures, from saturation values to hypoxia and in the temperature range of 11.7 to 33.3 °C. Especially in the confined sites, sediments can exert an important depleting action on dissolved oxygen already at water temperatures above 20 °C, which are not particularly high for the lagoon.